Politik Identitas Di Indonesia: Antara Nasionalisme Dan Agama - Febriansyah, Bilal Ahmad; Manando, Ilham; Kusuma, Angga Wira (VIVA THEMIS, 2024)
Liberal democratization is also politically the basis for individual self-actualization. The guarantee of individual liberties in Indonesia's constitution reflects the popularity of this democratic system. However, this freedom ultimately clarifies the divide between identities (religion, ethnicity, language, gender, etc.) that exists in Indonesia, especially in relation to national political issues. Issues of state religion and nationalism are her two identities currently being debated in Indonesia. The politics of identity politics narrows until truthful claims emerge that one interest group is superior to another, and this interest issue begins to divide nations that previously maintained their differences. This article aims to shed light on the reality of identity politics in Indonesia today, focusing on two identity groups: religious groups and nationalist groups. Qualitative methods and literature surveys are used to answer this question. This study finds that the divisions created by political groups based on religious identities and nationalism are constrained by the emergence of crises of trust in government, the spread of false reports, persecution, betrayal, democratic space, etc. found to lead to stability disruptions.